Tillage Study for Corn and Soybeans: Comparing Vertical, Deep, and No-Tillage - E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2018)
Trends from a tillage study conducted since 2011 are beginning to show that corn yields are greater when there is an occasional deep tillage. The yield of soybeans have not been affected significantly by tillage systems ranging from no-till to conventional tillage every year.
Keywords: Tillage; vertical tillage; corn; soybeans